Gae mi heo li - Heo, Eun Mi (Kookmin Books, 2007)
Once upon a time, ants relied upon a rabbit to survive. One day the rabbit thought of the idea how to free itself from the ants. Now we can explore why the ant's waist is so tiny
In korean. Schr.
Keywords: Ants / Juvenile fiction; Rabbits / Juvenile fiction; Wisdom / Juvenile fiction; Ants; Rabbits; Wisdom; Ameisen; Sozialverhalten; Freiheit; Nahrung; Bilderbuch